Comparing Albuminuria and High Sensitivity C-Reactive Protein as Predictors of Silent Myocardial Ischemia in Hypertensive Men without Diabetes Mellitus. (June 2015) - Winata, Johan; Supit, Alice; Rotty, Monique; Elka, Kana Kurniati; Kuncoro, Hendro Adi; Abd.Azis, Razak; Panda, Agnes Lucia
Abstract : Background: Albuminuria has been proven as an independent risk factor for SMI in diabetes, but its role in hypertensive patients without diabetes is unclear. High sensitivity C-reactive protein (hs-CRP) has been proven as an established predictor for coronary artery disease, but its role as predictor for asymptomatic myocardial ischemia in hypertensive subjects is not known. Objectives: This study is aimed to determine the correlation between albuminuria and hs-CRPto SMI in hypertensive patients without diabetes. Methods: Fourty consecutive asymptomatichypertensivemen, aged 40–60 years, without diabetes and known CAD were included. They underwent treadmill stress testing (TST) and collection of spot urine and blood sample to measure albumin urine to creatinine ratio (ACR) and hs-CRP level. SMI was diagnosed if ischemic criteria of TST was met without anginal symptom. ACR ≥ 20 mg/g was considered albuminuria positive. The cut off value for positive hs-CRP was ≥ 3 mg/dL. Results: SMI was diagnosed in 15% patients. Albuminuria was significantly associated with SMI (OR 13.889 (95% CI 1.423 – 135.544), p value = 0.014). ROC curve analysis demonstrated the area under the curve (AUC) = 0.784 ([95% CI 0.588–0.98], p value= 0.028). The subsequent calculated sensitivity, specificity, positive- and negative-predictive value of albuminuria to predict SMI were 83.3%, 73.5%, 35.7%, and 96.2% respectively. On the other hand, no significant correlation was found between hs-CRP and SMI ( p  = 0.099). Conclusion: Albuminuria, but not hs-CRP, is a good tool for excluding SMI in asymptomatic hypertensive men without diabetes.